(untitled) (Stato, Chiese e pluralismo confessionale, 2014)
Contributo sottoposto a valutazione SOMMARIO: 1. Introduzione – 2. La dottrina canonistica (con cenni dottrinali psichiatrici) e i disturbi del comportamento alimentare – 3. Le sentenze del Tribunale Ecclesiastico Regionale Lombardo e i disturbi del comportamento alimentare – 4. Le sentenze del Tribunale Ecclesiastico Regionale Triveneto e i disturbi del comportamento alimentare – 5. Conclusioni. ABSTRACT Eating disorders and canonical marriage. The experience of Lombardo and Triveneto Ecclesiastical Regional Courts Eating disorders find an increasing prevalence in the current social context and inevitably the impact that they have on the person who suffers is also reflected on the theme of the canonical matrimonial consent, placing itself in the bed of can. 1095 CIC. In this context the work wants to offer an overview of decisions in matters of Ecclesiastical Regional Courts, in particular Lombardo and Triveneto, paying attention to the legal evaluation of the consequences that these pathologies may have on the capacity to contract a valid canonical marriage.